O modelo 331 mínimo reduzido - Ferreira Júnior, José Geilson (2012)
The Standard Model of elementary particles has been verified by all experimental tests up to the present moment. However, theoretical and experimental evidences guarantee us that this model is not the final one that describes the fundamentals interactions. In this way, the aim of this work is to develop model based on the gauge group (3)⊗(3)⊗ () (331 model), a simple extension of the gauge group of the Standard Model, which solves some problems not covered by this model. There are many versions of 331 model well-founded, one of these is the minimal version, which leptonic content is identical to the Standard Model. In the minimal 331 model, the scalar sector is formed by three triplets and one sextet of scalars, which leads to large amount of interactions, so this proposal complicates the phenomenology of the scalar sector. In my work, we shall show that the structure of the minimal 331 model can be constructed with only two triplets. In relation to the later model, our model presents some advantages, like making the phenomenology of the scalar sector more tractable.